Prevalence of Arm Lymphedema among Patients with Breast Cancer Surgery - Pandey, Radha Acharya; Shrestha, Shilpa (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Lymphedema is a common complication of cancer therapeutics; its prevalence, treatment outcomes, and costs have been poorly defined. It is potentially debilitating condition in breast cancer survivors which negatively affects the quality of life. This study aims to assess the prevalence of arm lymphedema among patients with breast cancer surgery. Materials & Methods: A cross-sectional study was conducted to assess the prevalence of arm lymphedema among the women with breast cancer surgery. Purposive sampling technique was used to collect the data from a sample of 66 women of selected hospitals. Data were collected through self constructed structured and semi structured interview based questionnaire which consisted socio demographic information and clinical related factors. Results: Among The overall prevalence of arm lymphedema was found to be seven (10.6%) respondents among the study population. In this study, 41 (62.1%) respondents were < 50 years of age, 13 (19.7%) had education of secondary level, 27 (40.9%) had received radiation therapy, 63 (95.5%) had no history of infection, 54 (81.8%) had undergone modified radical mastectomy, and 56 (84.8%) had involved lymph node resection. Statistically no any significant association was found between these variables. Conclusion: On the basis of the findings, this conclusion has been drawn that prevalence of arm lymphedema among patients with breast cancer surgery was low (10.6%). Moreover no association was found between the prevalence of arm lymphedema, sociodemographic variables and clinical related factors.